Administration of Micro-credit by National Bank - Rajkumar, K. Prabakkar (Ushus Journal of Business Management, 2007)
The United Nations has designated the year 2005 as the "International year of Micro-Credit". The Micro Finance (MF) initiatives of NABARD have evolved as a sustainable social movement over a decade by now. The design and content of these innovations have remained dynamic in tandem with the changing needs of the micro finance sector in the Country. These initiatives have attracted the attention of a wide range of stakeholders. Large number of formal and informal agencies has joined the NABARD in this unique process of soda-economic engineering. The relevance of the micro finance programme was greatly enhanced the interest of all participants through the core strategies of SHG — bank linkage, which was built around a simple but basic aspect of human nature — the feeling of self-worth.